FINANCIAL SUPPORT AS A DETERMINANT OF SMALL AND MEDIUM-SIZED ENTERPRISES ECONOMIC GROWTH - Vapa Tankosić, Jelena; Volf, Dejan; Ignjatijević, Svetlana (International Journal of Economic Practice and Policy, 2021)
Abstract: European Union integration and revitalization of economy after the global economic crisis require small and medium-sized enterprises in Republic of Serbia to face more complex and dynamic environment which requires greater competitiveness in terms of improved quality, efficiency and management practices. However, the competitiveness of the regional SMEs is still at a much lower level compared to other European SMEs. Pointing out to the characteristics of small and medium enterprises, a logical conclusion can be drawn that state support for this sector is important. When forming the support modalities, the whole sector should not be viewed unambiguously. This paper analyses the importance of financial and non financial support for SMEs in terms of organizational capability and competiveness. Roy’s test, Pearson’s coefficient of contingency (χ), and multiple correlation coefficients (R) are applied as univariate statistical procedures. By applying MANOVA and discriminant analysis, the results point out to a difference and clearly defined boundary between other forms of support and financial forms of support in all the analyzed units. The research results indicate that the financial forms of support for SMEs are perceived to impact the SMEs organization capability and competitiveness and the largest contribution of respondents’ unit favours the benefit of state institutions in forms of financial support.